Budaya Jaga Mayyit di Kuburan di Tinjau dari Hukum Islam (Studi Kasus Desa Racek Tiris Probolinggo) - Nanang Qosim (Asy-Syari’ah : Jurnal Hukum Islam, 2017)
Culture is a way of life that is developed and shared by a group of people and passed down from generation to generation (generation to generation). Cultures are made up of intricate elements, including religious systems, and politics, customs, language, tools, clothing, buildings, and artwork. Language, unification as well as culture, is a part that can not be separated from human beings so that many people tend to be considered genetically inherited. See the cultural definition by Koentjaraningrat handover Budiono K, forcefully, “according to anthropology, culture is all the system of ideas and taste, actions, and works produced by humans in the life of society, which is his own by learning. This understanding means the inheritance of ancestral cultures through the process of education. When a person tries to communicate with people of different cultures and adjusts the differences, prove the culture is learned. Culture is strongly strengthened dengn masyarakat. Culture is a lifestyle thorough, abstract, and broad. Many cultural aspects contribute to communicative behavior. These socio-cultural elements and many human social activities.